2012
DOI: 10.1002/jat.1790
|View full text |Cite
|
Sign up to set email alerts
|

Developing in vitro reporter gene assays to assess the hormone receptor activities of chemicals frequently detected in drinking water

Abstract: The present study intended to develop receptor-mediated luciferase reporter gene assays to evaluate and compare the estrogen receptor (ER), androgen receptor (AR) and thyroid hormone receptor (TR) activities of target chemicals. Di-2-ethylhexyl-phthalate (DEHP), chlorpyrifos (CPF), 2,4-dichlorophenoxyacetic acid (2,4-D) and bisphenol A (BPA) are some of the most common contaminants in drinking water and are frequently detected in China and worldwide. The chemicals were tested at concentrations of 0.1, 1, 10 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 43 publications
1
4
1
Order By: Relevance
“…No alterations in AGD were reported in rat offspring exposed to 2,4-D in utero and during lactation [58]. 2,4-D did not interact with estrogen or androgen receptors or steroidogenesis pathways in vitro [8,59] but the herbicide was reported to potentiate the activity of testosterone through the androgen receptor [8], which would be expected to increase AGD in males in contrast to the decrease observed in our study. Overall, the evidence for a direct interference with sex hormone receptors or steroidogenesis at relevant dose-levels for the pesticides included in this study is limited.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…No alterations in AGD were reported in rat offspring exposed to 2,4-D in utero and during lactation [58]. 2,4-D did not interact with estrogen or androgen receptors or steroidogenesis pathways in vitro [8,59] but the herbicide was reported to potentiate the activity of testosterone through the androgen receptor [8], which would be expected to increase AGD in males in contrast to the decrease observed in our study. Overall, the evidence for a direct interference with sex hormone receptors or steroidogenesis at relevant dose-levels for the pesticides included in this study is limited.…”
Section: Discussioncontrasting
confidence: 87%
“…All these pesticides are non-persistent with biologic half-lives of hours to days and they are able to cross the placenta in humans [5]. In experimental studies, 2,4-D and some organophosphates and pyrethroids have been identified as potential endocrine disruptors with capacity to interfere with sex hormone action [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered that phthalates exert their action by inhibiting Leydig cell synthesis of testosterone, but in vitro studies have shown both androgenic and anti-androgenic effects at the receptor level, are dependent on the concentration and mixture of the metabolites (Akingbemi et al, 2004;Christen et al, 2010Christen et al, , 2012Kruger et al, 2008;Sun et al, 2012). Our results are compatible with both mechanisms.…”
Section: Discussionsupporting
confidence: 86%
“…While Oakes et al (2002) 33 , reported no significant difference in the serum concentration of testosterone in control animals when compared to treated animals, they noticed a severe reduction in testicular weight in some high dose animals with histology showing shrunken tubules with germ cell depletion. In addition, Sun et al (2012) 34 , conducted gene assays and found that 2,4-D showed no agonist or antagonist activity but it significantly enhanced the activity of testosterone through androgen receptors. Liu et al (1996) 35 also reported no effects of 2,4-D on testosterone levels in rat Leydig cells when conducting the experiment in vitro.…”
Section: Discussionmentioning
confidence: 99%